The world is not enough [videorecording (DVD)] - Apted, Michael; Brosnan, Pierce; Marceau, Sophie, 1966- (MGM Home Entertainment, 2012)
After the murder of a Russian oil tycoon, James Bond vows to protect his daughter who has taken over her father's operation.